A personality test for the Filipino child panukat ng pakikipagkapwa ng batang Pilipino - Abenojar, Trinidad Opiniano 1935- (1980)
This research centered on the construction and development of a personality instrument, a personality test for the Filipino child. The instrument taps sixty five (65) items which were generated from children, aged 8 to 10, from the urban elementary school group in Quezon City: Balara Elementary School, Kamuning Elementary School, and Trinity College. The conceptual scheme that guided the research was inspired by Sullivan's Interpersonal Relationship Theory and the PARENT, ADULT, CHILD (PAC) Personality model presented by Harris. The findings of the study led to the conclusions that the personality instrument is reliable based on the high degree of stability of the responses, and that it is also valid such that it was able to distinguished between the boys and the girls and the second and fourth graders, and that the dimensions in the establishment and maintenance of good interpersonal relationships tend to be closely related.